Analisis Sanitasi Pasar Tradisional Barukoto di Kota Bengkulu - Elfira, Cindy; Yusmidiarti (Poltekkes Kemenkes Bengkulu, 2025)
Sanitation of the barukoto traditional market in bengkulu city has an important role in maintaining public health, but its condition has not meet environmental health standards according to the minister of health regulation no. 17 of 2020. This research aimed to know the sanitation condition of the barukoto market based on six aspects of healthy market assessment. The research method uses quantitative descriptive with an observational approach, using an environmental health inspection form (ikl) consisting of 131 indicators. Data was collected through direct observation and tabulated to calculate the percentage of standard compliance. Research results show that of 131 indicators, only 53 indicators (40%) meet the requirements. Assessment of each aspect is: location (80%), building (37%), sanitation management (25%), phbs (64%), security (87%), and supporting facilities (50%). With these values, market barukoto has not meet the criteria for a healthy market. The most problematic aspects are the building, sanitation system, and supporting facilities. While security is relatively good, it cannot compensate for the existing deficiencies. The conclusion of this study is that the barukoto market does not meet the requirements for a healthy market. Therefore, it is necessary to improve sanitation facilities, increase education on clean and healthy living behaviors (phbs), and conduct regular monitoring by health workers and market managers.